Democracy Assistance to Global South: A Case Study of Konrad-Adenauer Stiftung (KAS) Freedom Agenda in Indonesia - Tsabita Afifah Khoirunnisa; Yusli Effendi (Global South Review, 2023)
This paper aims to investigate and analyze the democracy promotion carried out by Konrad-Adanauer Stiftung (KAS) in Indonesia. Our provisional findings on the case show that the hegemony of the North over the South is also perpetuated through political and economic assistance. Through the German political foundation of KAS, Germany seeks to foster a Western "better democracy" in Indonesia through several programs in collaboration with local actors. These "Freedom Agenda '' include training for civil apparatus and legal drafting training for national legislation. The Freedom Agenda carried out by KAS in Indonesia is associated with Germany's pursuit of democracy promotion policy. This study utilizes Neo-Gramscian Approach by Coxian Critical Theory (CCT) to investigate the role of KAS in maintaining the hegemonic order of Western Democracy in Indonesia through Cox's historical structure. By using library research, this study seeks to explain the reciprocal relationship between Cox's social forces in hegemony structure of Western democracy.Keywords: Konrad Adenauer Stiftung; democracy promotion; hegemony; social forces